2013
DOI: 10.1590/s1519-38292013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao atraso do desenvolvimento motor de crianças prematuras internadas em unidade de neonatologia

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1
24

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
1
8
1
24
Order By: Relevance
“…There was no significant influence on this research in the number of PN consultations on ND, however, this result does not corroborate the findings by Araújo et al 10 which evaluated premature infants hospitalized in neonatal units, and showed that a high number of pre-natal consultations was linked to delayed motor development of children. This result can be explained by the fact that most of the women who received more PN monitoring had more risk factors during pregnancy 10 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…There was no significant influence on this research in the number of PN consultations on ND, however, this result does not corroborate the findings by Araújo et al 10 which evaluated premature infants hospitalized in neonatal units, and showed that a high number of pre-natal consultations was linked to delayed motor development of children. This result can be explained by the fact that most of the women who received more PN monitoring had more risk factors during pregnancy 10 .…”
Section: Discussioncontrasting
confidence: 99%
“…This result can be explained by the fact that most of the women who received more PN monitoring had more risk factors during pregnancy 10 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Prolonged use of MV may lead to the establishment of other respiratory illnesses (37,38), in addition to low motor performance (38), probably due to limiting the variation in positioning the child in their spontaneous movement and postural adjustments. These early experiences can have repercussions on their functional abilities, especially in the areas of self-care and mobility due to possible injury in the upper airway, underdevelopment of musculoskeletal, neurological and sensory systems, whose integrity is essential for execution of activities in these areas.…”
Section: Discussionmentioning
confidence: 99%